Strategies to Improve Goat Production in India - Thiruvenkadan, A. K.; Rajendran, R. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Goat husbandry in India is essentially an endeavor of millions of small holders who rearÂ aials o Cop â€˜esidues ad Coo Popet â€˜esoues. Idia has ih eposito of goatgenetic resources with 24 recognized breeds and a large proportion of non-descript or mixed breeds.The poo as oâ€ goat has teedous potetial to e pojeted as the Futue Aial fo ualprosperit ude the hagig agoâ€geoâ€liati oditios ad depletig esoues i Idia. Thee isgeat sope fo eaig goats fo eat podutio ude seiâ€itesie ad itesie sstes ofmanagement. With shrinking resources and increasing demand of goat meat and milk, there is anurgent need to genetically improve and manage these animals through modern scientific tools toenhance their productivity. The future of goat breeds in India lies in the appropriate approaches toconservation, combining a number of integrally related components and effective action programsapproached holistically for successful conservation of goat genetic resources. The proper breedingstrategy needs to be adopted after anticipating and identifying those forces that drive goatproduction system for high productivity in India.Key Words: Goat Breeds, Genetics Improvement, Strategies